Effects of electronic health record use on the exam room communication skills of resident physicians: a randomized within-subjects study. (21st October 2014) - Taft, Teresa; Lenert, Leslie; Sakaguchi, Farrant; Stoddard, Gregory; Milne, Caroline
Abstract: Background The effects of electronic health records (EHRs) on doctor–patient communication are unclear. Objective To evaluate the effects of EHR use compared with paper chart use, on novice physicians' communication skills. Design Within-subjects randomized controlled trial using observed structured clinical examination methods to assess the impact of use of an EHR on communication. Setting A large academic internal medicine training program. Population First-year internal medicine residents. Intervention Residents interviewed, diagnosed, and initiated treatment of simulated patients using a paper chart or an EHR on a laptop computer. Video recordings of interviews were rated by three trained observers using the Four Habits scale. Results Thirty-two residents completed the study and had data available for review (61.5% of those enrolled in the residency program). In most skill areas in the Four Habits model, residents performed at least as well using the EHR and were statistically better in six of 23 skills areas (p<0.05). The overall average communication score was better when using an EHR: mean difference 0.254 (95% CI 0.05 to 0.45), p = 0.012, Cohen's d of 0.47 (a moderate effect). Residents scoring poorly (>3 average score) with paper methods (n = 8) had clinically important improvement when using the EHR. Limitations This study was conducted in first-year residents in a training environment using simulated patients at a single institution. Conclusions Use of an EHR on a laptop computer appears to improve the ability of first-year residents to communicate with patients relative to using a paper chart.